Effect of Temporary Meiotic Attenuation of Oocytes with Butyrolactone I and Roscovitine in Resistance to Bovine Embryos on Vitrification - Maziero, R. R.D. [UNESP]; Guaitolini, C. R.F. [UNESP]; Paschoal, D. M. [UNESP]; Kievitsbosch, T.; Guastali, M. D. [UNESP]; Moraes, C. N. [UNESP]; Landim-Alvarenga, F. C. [UNESP] (Wiley, 2016)
Contents: This study aimed to produce in vitro bovine embryos by the addition of two drugs, which is responsible for oocyte meiosis inhibition: roscovitine (ROS) and butyrolactone I (BL-I). Oocytes were recovered from slaughtered cows and matured in a commercial medium and maintained in a 5% CO2 atmosphere. Oocytes were maintained for 6 h in an in vitro maturation (IVM) medium containing ROS (12.5 μm), BL-I (50 μm) and association of drugs (ROS 6.25 μm and BL-I 25 μm). Oocytes were cultured for 18 h in an agent-free medium for the resumption of meiosis. After 24 h of maturation, oocytes were inseminated in the commercial in vitro fertilization (IVF) medium. Presumptive zygotes were cultured in SOFaa medium in a 5% CO2 atmosphere. On day 3, rate of cleavage was evaluated and on days 6 and 7, rate of blastocyst formation. BL-I and its association with the ROS increased the rates of cleavage and blastocyst formation (p < 0.05). The ROS alone was inefficient, impairing embryonic development, with low rates of blastocyst formation when compared to the control group and other treatments (p < 0.05). The embryos from BL-I and ROS+BL-I groups presented higher number of cells and lower rates of cellular apoptosis compared to other groups, either for the fresh or for post-thawing embryos. Embryos from ROS+BL-I group showed to be more resistant to the vitrification process, presenting a higher rate of embryonic re-expansion (p < 0.05). In conclusion, block of meiosis using BL-I or its association with ROS increased the rate of blastocyst formation, and the association of ROS+BL-I resulted in a better resistance to the embryo cryopreservation process.